Limestone Resource Estimation Using Block Model Approach in the Wuluhan Area, Jember Regency, East Java Province - Sapto Heru Yuwanto; Yazid Fanani; Sinaga Erlin Cristin; Alfian Adii; Gilberto Amaral (Journal of Applied Sciences, Management and Engineering Technology, 2026)
The research location is in an IUP area of 142.23 Ha owned by PT. Gunung Kelabat Citra Abadi located in Lohjejer Village, Wuluhan District, Jember Regency. The IUP area used as the research location has limestone potential based on the lithology that composes the area and the ongoing exploration activities, but the ongoing exploration activities have not yet carried out limestone resource estimation. Based on this background, the purpose of this research is to determine the geological conditions and rock characteristics in the Mining Business Permit area, the direction of limestone resource distribution, and limestone resource estimation. The analysis of geological conditions and the direction of limestone distribution is based on geological mapping activities combined with subsurface geological data, limestone characteristics are based on the results of laboratory testing of physical and mechanical properties of rocks, while resource estimation is carried out using the block model method. The results of the analysis show that the geological conditions in the IUP area are relatively simple, reflected by the geological structure in the form of minor fractures, and variations in lithology which are divided into limestone breccia and reef limestone, with limestone characteristics having a compressive strength value between 428,690 kg/cm2 – 483,447 kg/cm2, and an internal friction angle value of 14o – 25.03o, and a measured resource estimate of 181,032,021 Tons consisting of a limestone breccia volume of 70,969,553 tons and a reef limestone volume of 110,062,467 tons minus a soil volume of 2,241,105 tons.